Menjalin Kerukunan Perbedaan Gereja Ditengah-tengah Masyarakat Pada Masa Kini Di Desa Parhorboan, Kecamatan Pagaran (International Forum of Researchers and Lecturers, 2024)
This research aims to analyze efforts and strategies in establishing inter-church harmony in society during the current pandemic. The current pandemic creates new challenges in maintaining interfaith relations and strengthening tolerance in communities. In this context, churches from various denominations are faced with the need to increase collaboration and mutual understanding. This research uses a qualitative approach by conducting in-depth interviews with church leaders and community members who are actively involved in efforts to establish harmony. Thematic analysis was conducted to identify key patterns in practices that support inter-church harmony. This research makes an important contribution to the understanding of how churches can work together to create harmony in difficult times such as the current pandemic. The practical implications of this research can be a guide for church and community leaders in building harmonious relationships amidst the challenges they face together. The research results show that there are several key factors that support the success of efforts to establish church harmony today. Among these are regular inter-religious dialogue, joint social activities, and an inclusive approach in understanding differences in beliefs.